Prediction of stump healing in lower limb amputation: a narrative review. (1st December 2019) - Ashraff, Suhel; Siddiqui, Muhammad A; Santos, Derek; Carline, Thomas
Abstract : Both types of diabetes, as well as different forms of acquired diabetes, are associated with diabetic peripheral neuropathy. Diabetic foot ulcers (DFU) is the condition most commonly related to somatic peripheral neuropathy, often leading to gangrene and limb amputation. Independent from large-vessel disease, sensory loss may result in DFU development and even amputation. The crucial part of any lower limb amputation is the stump healing process, which represents the central goal of postoperative management. Despite the importance attributed to this process, a standard set of guidelines regarding efficient healing methods is yet to be formulated. Health professionals are faced with the challenge of assessing the different risk factors and deciding which has a greater influence on the stump healing rate. There is currently an insufficient number of studies regarding factors effecting lower limb amputation. The main purpose of this review is to discuss the markers that can be helpful in the prediction of stump healing in patients who have undergone lower limb amputation.